The Attitude of Shia Marjai in The Poltical Process of Iraq After 2014 - Rekar Hassan Mohammed; Sabah Subhi Haydar (QALAAI ZANIST JOURNAL, 2022)
The decision-making process is a complex process that passes through several stages and is influenced by many external and local factors. There are many factors that influence the decision-making process in Iraq, one of which is the Shiit supreme Marjah, which is superior to those parties and actors who have an important role in decision-making. This role is performed within the framework of counseling, and appears after the collapse of Saddam Hussein's regime in 2003. But after the emergence of ISIS and its threats and dangers, the political role of the Shiite supreme Marjah appeared more and more through the fatwa to counter ISIS.